Empowerment Of The GMIT Sion Kefamenanu Youth Group Through Eco-Friendly Kampung Chickens Farming - Charles Venirius Lisnahan; Steffanie Merlin Clyricia Noach; Lukas Pardosi; Wilda Lumban Tobing (LPPM Universitas Timor, 2026)
The purpose of this community service is to improve the knowledge, skills, income and welfare of the Partner Group in the PKM youth empowerment program of GMIT Sion Kefamenanu through environmentally friendly Kampong chicken cultivation. This community service was carried out at the GMIT Sion Kefamenanu Youth Group, East Nusa Tenggara. The method used is participatory action research, partner groups, religious leaders and the Implementation Team together determine the type of activity and implementation of activities in the field based on the urgency and priority of the problem. Solutions to the problems are based on the results of the initial situation analysis and adjusted to the needs and existing conditions. For this reason, socialization, training, technology application, evaluation and sustainability of the program are carried out. Extension activities, training/mentoring and practical implementation of activities aim to improve the group's abilities and skills. Mentoring activities include maintaining starter phase Kampong chickens in brooding cages and preventing disease with vaccination, maintaining the grower and pullet phases, making complete feed in the form of mash, crumble and pellets, drying feed with an oven and making bokashi fertilizer using cage waste. The results obtained in this PKM activity are that there has been a change in social behavior, knowledge and skills of youth groups in cultivating village chickens, including being proficient in handling chicks in brooding, handling growth phase chickens (growers and pullets), making complete crumble and pellet feed and being skilled in making bokashi fertilizer.